Combination of aerobic exercise and Hibiscus sabdariffa Linn. increased nitric oxide in rats - Adriani, Donna; Siagian, Minarma; Irawati, Dewi (Faculty of Medicine, Trisakti University, 2017)
Background Hypertension and myocardial infarction account for the high rate of mortality globally. Hibiscus sabdariffa (HS) Linn. is rich in antioxidants and previous studies have demonstrated its anti-hypertensive effects. Several studies show that regular physical activity is an important component to reduce cardiovascular mortality. The objective of this study was to evaluate the effects of a combination of aerobic exercise and HS extract on nitric oxide (NO) and endothelin-1 (ET-1) in rats.Â MethodsAn experimental study was conducted on 36 male Wistar rats, aged 4 weeks and 60-70 g in weight. The interventions were aerobic exercises and HS at 400 mg/kg BW/day administered for 4, 8 and 12 weeks. The rats were randomized into 12 groups: 3 control groups (C4, C8, C12), 3 aerobic exercise groups (A4, A8, A12), 3 HS groups (H4, H8, H12), and 3 combination groups [aerobic exercise and HS] (HA4, HA8, HA12). After 4, 8, and 12 weeks, the rats were sacrificed and their abdominal aorta was collected for determination of nitric oxide and ET-1 concentrations. One way ANOVA was used to analyze the data.Â ResultsThere was a significant difference in NO levels between all groups, with the 4-week aerobic exercise group (A4) showing the highest NO levels compared to the other eleven groups (p<0.05). In contrast, the ET-1 levels were not significantly different between all groups.Â Conclusions This study demonstrated that the combination of HS supplementation and aerobic exercise increases NO in rats, and provided further evidence to the traditional use of the plant as an antioxidants agent.